ANALYSIS OF VARIOUS ASPECTS OF OLIVE EXPORTS BASED ON PORTER'S DIAMOND MODEL (Singaporean Journal of Business Economics and Management, 2013)
Today for being a part of a truly global economy and maintaining our standard of living, we must learn to compete in an ever tougher world market place. That's why higher productivity and product quality have become essential. International trade is one of the important subjects in economic development; It can provide export incomes for investment and attract new technology to increase the productive potency in country. The focus of this article is on the debate as to whether or not Iran compete internationally in agricultural export product, Specifically the olive by using Porter's Diamond Model as proclaimed by Porter (1990)(10).